Assessment of Levels, Speciation, and Toxicity of Trace Metal Contaminants in Selected Shallow Groundwater Sources, Surface Runoff, Wastewater, and Surface Water from Designated Streams in Lake Victoria Basin, Uganda. (23rd May 2019) - Bakyayita, G. K.; Norrström, A. C.; Kulabako, R. N.
Abstract : The levels, speciation of elements, and toxicity of selected trace metals as well as other parameters in selected surface water, shallow groundwater sources, landfill leachate, and associated surface runoff in the Lake Victoria basin, Uganda, were studied. The WHO guidelines, Ugandan standards, Canadian guidelines and Swedish EPA were used for assessment. The shallow groundwater was acidic with pH values below 6.5. The pH, dissolved organic carbon, flouride, and sulphate levels for all springs were below the guideline values although 52.8% was contaminated with nitrates while 39% was contaminated with chloride ions. Some surface water samples had levels of major elements, such as iron, chromium, aluminium, and manganese, above the guideline values. Speciation studies showed that 74% of the metal ions was bound to dissolved organic matter in surface water, whereas in landfill leachates, the dominant ionic species was metal hydroxides or fulvic acid bound. Risk analysis based on the Swedish EPA showed varied risks of negative effects in 30%–76% of the sample sites ranging from high to increased risk in surface water, whereas the results from modelling sorption data using the Bio-met tool showed potential risk to toxicity effects of Cu 2+, Ni 2+, Zn 2+, and Pb 2+ in 15.3%–30.8% surface water samples and 8.3%–62.5% groundwater samples.